2020
DOI: 10.29252/pbp.2.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin, halal or haram? Gelatin, halal or haram?

Abstract: Gelatin is a solid and transparent material that has wide application in various industries, especially for the production of food and pharmaceutical. This material is mainly made from meat, skin and bones of pigs and cows around the world. The industrial process of gelatin production is a long and costly process Also; these sources of gelatin production are prohibited in many religions and cultures in the world and they have a lot of health hazards. Therefore, this study was aimed at reviewing the alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…It was shown that PCL/Gel scaffolds are not perfect candidates for skin wound repair due to their poor antibacterial properties and inappropriate water vapor transmission rate, and they may also need a protective membrane as the top layer 75 . On the other hand, pig‐ and cow‐derived Gel can cause allergic sensitivities in medical products, because this type of Gel contains IgE 76 …”
Section: Natural Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that PCL/Gel scaffolds are not perfect candidates for skin wound repair due to their poor antibacterial properties and inappropriate water vapor transmission rate, and they may also need a protective membrane as the top layer 75 . On the other hand, pig‐ and cow‐derived Gel can cause allergic sensitivities in medical products, because this type of Gel contains IgE 76 …”
Section: Natural Polymersmentioning
confidence: 99%
“…75 On the other hand, pig-and cow-derived Gel can cause allergic sensitivities in medical products, because this type of Gel contains IgE. 76…”
Section: Gelatinmentioning
confidence: 99%
“…Gelatin is mainly an unmodified hydrolyzed collagen in which the collagen protein is converted to smaller peptides. Gelatin has a wide molecular weight range in relation to physical and chemical methods of denaturation based on what kind of hydrolysis process is used in its production (Elyasi et al, 2020).…”
Section: Definition Of Gelatinmentioning
confidence: 99%
“…Apart from that, gelatin also has a unique amino acid composition and structure that provides functional properties (Amertaningtyas et al, 2019). Commonly, gelatin is used as a gelling agent in the food, pharmaceutical, photographic, and cosmetic industries (Elyasi et al, 2020). In particular, gelatin distinctive structure of amino acids is able to provide several medical benefits and the form of gelatin can vary.…”
Section: Definition Of Gelatinmentioning
confidence: 99%
See 1 more Smart Citation